Data-driven probabilistic post-earthquake fire ignition model for a community. (December 2017) - Elhami Khorasani, Negar; Gernay, Thomas; Garlock, Maria
Abstract: Fire following earthquake (FFE), a cascading multi-hazard event, can cause major social and economical losses in a community. In this paper, two existing post-earthquake fire ignition models that are implemented in Geographic Information System (GIS) based platforms, Hazus and MAEViz/Ergo, are reviewed. The two platforms and their FFE modules have been studied for suitability in community resiliency evaluations. Based on the shortcomings in the existing literature, a new post-earthquake fire ignition model is proposed using historical FFE data and a probabilistic formulation. The procedure to create the database for the model using GIS-based tools is explained. The proposed model provides the probability of ignition at both census tract scale and individual buildings, and can be used to identify areas of a community with high risk of fire ignitions after an earthquake. The model also provides a breakdown of ignitions in different building types. Finally, the model is implemented in MAEViz/Ergo to demonstrate its application in a GIS-based software. Highlights: Fire Following Earthquake modules in Hazus and MAEViz/Ergo are investigated. A probabilistic post-earthquake fire ignition model is proposed based on historical data. The proposed model provides results at census tract and individual building levels. The model and a GIS-based platform can be used to evaluate resiliency of a community.